Simulation and experimental study of double holes film cooling - Aminnuddin, Mohd Hazim Fadli (2017)
In the modern gas turbine, film cooling has been widely used to provide thermal protection for the external surface of the gas turbine blades. Numerous number of geometrical arrangement film cooling have been presented for the past 50 years. The main inspiration of the presented geometrical arrangements film cooling are to minimize the effect of lift off phenomena caused by the formation of the Counter Rotating Vortex Pair (CRVP) which commonly discovered in the Single Cylindrical Hole (SCH) arrangement. In order to reduce the CRVP effects, tremendous efforts from the past researchers have been made including the introduction of the Double Cylindrical Hole (DCH). The present study has made use this DCH along with the employment of several geometrical arrangements including pitch distance (POD), length between holes in streamwise direction (LoD), compound angle and upstream ramp. The evaluation of these parameters involved three different blowing ratios, M and two value of the turbulence intensities, Tu. The diameter of the cooling holes in the present study is 4.75mm which taken based on the previous study. The present study has been divided into two major studies namely experimental study and simulation study. The purpose of the experimental study is to validate the present simulation study which making use of an open end wind tunnel. As the validation process shows a good agreement results, 14 more models have been built and tested using simulation study which the total cases considered are 105. As for the result, all the considered cases of DCH shows improvement in comparison with SCH. Each of the considered geometries and flow parameters have their own effects on the film cooling effectiveness which will be elaborate in details in the further chapter. As conclusion, the simulation is having good agreement with the present experimental study and the previous study which is essential to confirm the reliability of the study. Meanwhile, all DCH shows improvement in term of film cooling effectiveness on each of blowing ratio value.